2003
DOI: 10.1128/jcm.41.4.1750-1752.2003
|View full text |Cite
|
Sign up to set email alerts
|

New PCR Test That Recognizes All Human Prototypes of Enterovirus: Application for Clinical Diagnosis

Abstract: We describe a new PCR test (Penter RT-PCR) that recognizes all 64 prototypes of enterovirus. Sixty clinical samples were analyzed in parallel with this Penter RT-PCR and previously described PCR tests: 34 and 32 samples tested positive, respectively. This assay is suitable for use in clinical diagnosis, and its ability to amplify all known serotypes makes it more useful than other consensus PCR tests.Enteroviruses (EVs) are small single-stranded RNA viruses that comprise 64 serotypes recently redistributed int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
2
20
0
1
Order By: Relevance
“…The specificity of the Penter RT-PCR system used for the detection of EV genomes in CSF was demonstrated in a previously published study (2). The sensitivity of the new one-step Penter RT-PCR test was estimated to correspond to 0.05 50% tissue culture infectious doses of poliovirus strain Sabin 2 per 140 ml, according to the protocol previously described by Andréoletti et al Of the 54 CSF specimens selected, 28 (52%) were positive for EV isolation from cell culture whereas 41 (76%) were positive by the in-house RT-PCR assay and 43 (80%) were positive by the new Penter RT-PCR test (52 versus 76 versus 80%; P ϭ 0.003).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The specificity of the Penter RT-PCR system used for the detection of EV genomes in CSF was demonstrated in a previously published study (2). The sensitivity of the new one-step Penter RT-PCR test was estimated to correspond to 0.05 50% tissue culture infectious doses of poliovirus strain Sabin 2 per 140 ml, according to the protocol previously described by Andréoletti et al Of the 54 CSF specimens selected, 28 (52%) were positive for EV isolation from cell culture whereas 41 (76%) were positive by the in-house RT-PCR assay and 43 (80%) were positive by the new Penter RT-PCR test (52 versus 76 versus 80%; P ϭ 0.003).…”
mentioning
confidence: 99%
“…In the present study, we evaluated a new commercially available RT-PCR assay which utilizes the principle of stair primers located in the 5Ј uncoding region to amplify EV genomes (5), detects the EV amplicons in a microwell colorimetric assay within 10 h, and demonstrates the absence of PCR inhibitors by using a positive control tested with a duplicate sample after RNA extraction. This new Penter RT-PCR method has been evaluated in a recent study that demonstrated its ability to recognize all 64 prototypes of human EV strains but not parechovirus 1 and 2 (2). In this study, we used a modified version of this EV amplification method that allows a one-tube RT-PCR amplification of EV genomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Thus, the incidence of enterovirus infections might have been higher if surveillance samples were subjected to more sensitive assays such as RT-PCR, 12,25 but the fact remains that enteroviruses in this study were rarely associated in life-threatening complications. There are a number of possible explanations for these findings.…”
Section: Enterovirus Infection In Transplant Recipientsmentioning
confidence: 82%
“…The commercially available Enterovirus Penter RT-PCR test (''Enterovirus consensus kit new generation'', Argène Biosoft, Varhiles, France) utilizing several pairs of stair primers selected for an annealing in the highly conserved 5 0 untranslated region [Bourlet et al, 2003], was used according to the manufacturer's instructions (Argène Biosoft). This assay has been shown to be able to detect all the 65 human EVs [Bourlet et al, 2003].…”
Section: Detection Of Enterovirus Rna In Cervicovaginal Lavage Samplesmentioning
confidence: 99%